Perkembangan Jamaah Tabligh di Malaysia, 1970–1990-an Tablighi Jamaat’s Development in Malaysia, 1970–1990s (KEMANUSIAAN The Asian Journal of Humanities, 2018)
Tablighi Jamaat is a significant missionary movement towards disseminating of Islamic teaching in Malaysia. Participation of some Malay Muslim in Tablighi Jamaat in the 1970s demonstrated that Muslims were more concerned about Islam prior to that period. Hence, this paper discusses the background and challenges faced by the Tablighi Jamaat in the 1970s–1990s. Interviews were conducted with members and former members of Tabligh revealing that Islam adopted by Tabligh is relevant for Muslims in Malaysia as a manifestation of the life that is more concerned with religious values. The strength of Tablighi Jamaat in implementing the Islamic mission caused both the government and Malay society to raise issues challenging their credibility based on reports published by civil agencies and local newspapers. This study appraises the defensive response by Tablighi Jamaat to resolve the allegations placed upon them as their strategy in perpetuating their preaching mission. Jamaah Tabligh merupakan komponen dakwah yang signifikan dalam mengembangkan ajaran Islam di Malaysia. Penyertaan sebahagian Muslim Melayu dalam Jamaah Tabligh pada tahun 1970-an memberi petunjuk bahawa kedudukan Islam mula diberi perhatian secara meluas berbanding sebelumnya. Sehubungan itu, makalah ini membincangkan latar belakang dan cabaran yang dihadapi oleh Jamaah Tabligh dalam menggerakkan dakwah pada tahun 1970-an hingga 1990-an. Temu bual yang dijalankan terhadap ahli dan bekas ahli Tabligh menunjukkan bahawa ajaran Islam yang diterapkan dalam Tabligh adalah relevan dengan kehendak Muslim di Malaysia sebagai manifestasi kepada kehidupan yang lebih mementingkan nilai beragama. Kemantapan Jamaah Tabligh melaksanakan usaha dakwah menyebabkan pemerintah dan masyarakat Melayu membangkitkan isu yang mencabar kredibiliti jamaah tersebut berdasarkan laporan agensi berkaitan serta liputan akhbar tempatan. Justeru, kajian ini menilai respons Jamaah Tabligh mengatasi dakwaan yang dilemparkan dalam posisi defensif sebagai strategi penerusan dakwah mereka.